Physical Vs. Virtual Classroom: A Comparative Study Of Teacher Effectiveness Before And During Covid-19 Pandemic - Singh, Bushra S. P. (Gyan Management Journal, 2020)
In the wake of the Covid-19 Pandemic, it became mandatory for educational insititutions to shift operations online and resume classes. In order to capture the difference in the quality of teaching arising due to the use of online platform, this study collected perceptions of teachers on their teaching effectiveness in the physical setting and the virtual environment. For this purpose, data was collected from 224 teachers using the Teacher Effectiveness Scale (Jani, Shahid, Thomas, Francis & Francis,2018). Descriptive Statistics, Paired Samples T-Test and Independent Samples T-Test were used for analysis. It was found that quality of teaching was significantly higher in traditional settings. Also, it was found that the teaching quality of female teachers was more severely affected than male teachers due to the use of online platforms. No differences in teaching quality between real and online classrooms were found across age groups and tenure. Suggestions for improvement include online training sessions for teachers where technical skills and online pedagogical skills may be imparted. This study has bridged an important gap by presenting a comparison of physical and virtual classrooms from the teacher’s perspective.